Coalescence in fused filament fabrication process: Thermo-dependent characterization of high-performance polymer properties. (June 2021) - Lepoivre, Arthur; Levy, Arthur; Boyard, Nicolas; Gaudefroy, Vincent; Sobotka, Vincent
Abstract: One of the major drawbacks of the thermoplastic Fused Filament Fabrication process (FFF) is the poor mechanical properties of the parts produced. This is mostly related to the macroporosities resulting from a limited coalescence between filaments. Coalescence is ruled by the viscosity and surface tension of a polymer. Thus, an accurate characterization of these two properties is required to model and optimize coalescence during filament deposition and cooling. In this work, a surface tension characterization procedure over a large temperature range (25–380 °C) is presented and applied to PolyEtherKetoneKetone (PEKK) material. Additionally, the Newtonian viscosity is characterized with rheometry. The coalescence is then simulated by coupling an existing semi-analytical model with a previously presented 2D heat transfer finite element simulation model. The results show the importance of the temperature dependent implementation of surface tension. Additionally, a parametric study provides an industrial understanding of the FFF process. Highlights: Surface tension of high performance PEKK polymer was characterized over a wide range of temperature (25–370 °C). The surface tension and Newtonian viscosity were implemented in a coupled heat transfer and coalescence model for FFF. Surface tension and its temperature dependence were proved to influence the coalescence phenomenon.